Jenis Tumbuhan Obat yang Dimanfaatkan Untuk Pasca Melahirkan Oleh Etnis Melayu Di Tanjung Pura Kabupaten Langkat, Sumatera Utara - Bela Yustika; Jamilah Nasution; Riyanto Riyanto (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2022)
Medicinal plants come from natural ingredients and are passed down from generation to generation. Ethnic Malay is one of the tribes who use plants for postnatal treatment. This study aims to identify the types of plants found in postpartum treatment by the Malay tribe in Tanjunpra, Langkat Regency, North Sumatra. The method used is descriptive qualitative and quantitative with emic and ethical approaches. In collecting sample data, we used the interview method and the selection of informants by means of "purpose sampling and snowball sampling". From the results of the investigation, found 40 types of medicinal plants spread over 23 families. Most species came from the ginger family (9 species) and the Rutaceae family (3 species). The part of the plant that is most often used as postnatal medicine is the rhizome, leaves and fruit. Most of the crops are cultivated by the community, so they are mainly used in the fields.